Increase the level of preparedness of qualified basketball players in the preparatory period - Volodymyr Gradusov; Artem Kuzminchuk (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to study the adaptation of basketball players of student teams to training loads during the preparatory period of the annual cycle of training on the parameters of motor qualities and functional readiness. Material & Methods: conducted a survey of 12 basketball players on the team (Sumy, the highest league of the Ukrainian Basketball Championship). The following research methods were used: theoretical analysis of literary sources, methods of mathematical statistics, anthropometry and pedagogical control. Result: dynamics of changes at the stage of preparation for the season is shown. It is established and observed that under the influence of training sessions in the examined basketball players, not only the optimization of the functional systems of their organism, but also the level of the functional state of the organism as a whole. Conclusion: assessment of the functional condition of the athlete's body should play an important role in the overall system of medical and biological control in connection with significant additional information on the state of their body and the possibility of timely correction of physical activity and the provision of preventive measures. It is determined that during the preparatory period the level of motor qualities and functional readiness of the basketball players increased.